Contrast agent-free functional magnetic resonance imaging with matrix pencil decomposition to quantify abnormalities in lung perfusion and ventilation in patients with cystic fibrosis - Doellinger, Felix; Bauman, Grzegorz; Roehmel, Jobst; Stahl, Mirjam; Posch, Helena; Steffen, Ingo G.; Pusterla, Orso; Bieri, Oliver; Wielpütz, Mark O.; Mall, Marcus A. (Frontiers in Medicine, 2024)
Background: Previous studies showed that contrast-enhanced (CE) morpho-functional magnetic resonance imaging (MRI) detects abnormalities in lung morphology and perfusion in patients with cystic fibrosis (CF). Novel matrix pencil decomposition MRI (MP-MRI) enables quantification of lung perfusion and ventilation without intravenous contrast agent administration. Objectives: To compare MP-MRI with established morpho-functional MRI and spirometry in patients with CF. Methods: Thirty-nine clinically stable patients with CF (mean age 21.6 ± 10.7yr, range 8-45yr) prospectively underwent morpho-functional MRI including CE perfusion MRI, MP-MRI and spirometry. Two blinded chest radiologists assessed morpho-functional MRI and MP-MRI employing the validated chest MRI score. In addition, MP-MRI data were processed by automated software calculating perfusion defect percentage (QDP) and ventilation defect percentage (VDP). Results: MP perfusion score and QDP correlated strongly with the CE perfusion score (both r=0.81; P<0.01). MP ventilation score and VDP showed strong inverse correlations with percent predicted FEV1 (r=-0.75 and r=-0.83; P<0.01). The comparison of visual and automated parameters showed that both MP perfusion score and QDP, and MP ventilation score and VDP were strongly correlated (r=0.74 and r=0.78; both P<0.01). Further, the MP perfusion score and MP ventilation score, as well as QDP and VDP were strongly correlated (r=0.88 and r=0.86; both P<0.01). Conclusions: MP-MRI detects abnormalities in lung perfusion and ventilation in patients with CF without intravenous or inhaled contrast agent application, and correlates strongly with the well-established CE perfusion MRI score and spirometry. Automated analysis of MP-MRI may serve as quantitative noninvasive outcome measure for diagnostic monitoring and clinical trials.